Community and family relationships across the transition to medical school: links to student adjustment - Rincon, Brenda; Bravo, Diamond Y.; Arnold, Elisha; Meza, Alexis; Camacho-Thompson, Daisy (Frontiers in Psychology, 2024)
Introduction Supporting students during the transition to medical school is crucial for their academic adjustment. However, there has been limited research on the protective role of community and family support during this transition, despite evidence of the benefits of supportive relationships in higher education. Guided by self-determination theory, the current cross-sectional study explored how changes in family and community relationships impact Cuban medical students' sense of belonging in their field and their grade expectations. Methods A total of 881 medical students (MAge = 21.51, SD= 2.23, range = 18–33; 54% female; 72.2% Cuban) participated in this study. Participants included students across 6 years of medical school (1st year = 14.8%, 2nd year = 10%, 3rd year = 24.1%, 4th year = 19.3%, 5th year = 11.8%, 6th year = 20%). Results Controlling for key demographics (e.g., student aid experience, family legacy, nationality, year in medical school, prior academic performance, gender, and offspring), our findings revealed that improvements in community relationships—rather than family relationships—were associated with higher levels of field belonging. Additionally, more extensive experience as a student aid and a greater number of family members with a medical background were linked to higher levels of field belonging and higher grade expectations. Notably, higher prior academic performance was associated with increased field belonging but did not affect grade expectations. Conversely, identifying as female was related to both higher field belonging and higher grade expectations. Discussion Our study highlights the importance of supportive community relationships for medical students' academic adjustment. We discuss the potential benefits of enhancing community relationships within medical school training programs.